Maintaining Cognitive Functioning in Healthy Seniors with a Technology-Based Foreign Language Program: A Pilot Feasibility Study - Ware, Caitlin; Damnee, Souad; Djabelkhir, Leila; Cristancho, Victoria; Wu, Ya-Huei; Benovici, Judith; Pino, Maribel; Rigaud, Anne-Sophie (Frontiers in Aging Neuroscience, 2017)
Researchers have hypothesized that learning a foreign language could be beneficial for seniors, as language learning requires the use of extensive neural networks. We developed and qualitatively evaluated an English training program for older French adults; our principal objective was to determine whether a program integrating technology is feasible for this population. We conducted a 4-month pilot study (16, 2- hour sessions) with 14 French participants, (9 women, 5 men, average age 75). Questionnaires were administered pre- and post-intervention to measure cognitive level and subjective feelings of loneliness or social isolation; however, these scores did not improve significantly. Post-intervention, semi-directive interviews were carried out with participants, and a content/theme analysis was performed. Five main themes were identified from the interviews: Associations with school, attitudes towards English, motivation for learning English, attitudes towards the program’s organization, and social ties. The program was found to be feasible for this age group, yet perceived as quite difficult for participants who lacked experience with English. Nonetheless, most participants found the program to be stimulating and enjoyable. We discuss different suggestions for future programs and future directions for foreign-language learning as a therapeutic and cognitive intervention.